Religion and State in the Perspective of Islamic Thought - Supriyanto Supriyanto (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2020)
The discourse on the relationship between religion and state in Islam has been going on for quite some time since the era of the companions of the Prophet, the scholars from the classical era to the contemporary era. The era of the Companions of the Prophet was represented by the Shia, Khawarij and Mu'tazilah groups who had different views on the relationship between religion and state. The classical era was represented by well-known scholars namely Farabi, Mawardi, Ghazali, Ibn Taymiyah and Ibn Khaldun who also had different perspectives on the relationship between religion and state. Likewise, contemporary Muslim scientists present many religious views on the relationship between religion and state. Therefore, this paper will portray how the views of the three groups, some classical and medieval scholars, to modern-day intellectuals about the relationship between the two historically and by using a comparative critical-analysis approach through the perspective of islamic thought.